CuII(atsm) Attenuates Neuroinflammation - Choo, Xin Yi; Liddell, Jeffrey R.; Huuskonen, Mikko T.; Grubman, Alexandra; Moujalled, Diane; Roberts, Jessica; Kysenius, Kai; Patten, Lauren; Quek, Hazel; Oikari, Lotta E.; Duncan, Clare; James, Simon A.; et al. (Frontiers in Neuroscience, 2018)
Background: Neuroinflammation and biometal dyshomeostasis are key pathological features of several neurodegenerative diseases, including Alzheimer’s disease. Inflammation and biometals are linked at the molecular level through regulation of metal buffering proteins such as the metallothioneins. Even though the molecular connections between metals and inflammation have been demonstrated, little information exists on the effect of copper modulation on brain inflammation. Methods: We demonstrate the immunomodulatory potential of the copper bis(thiosemicarbazone) complex CuII(atsm) in an neuroinflammatory model in vivo and describe its anti-inflammatory effects on microglia and astrocytes in vitro. Results: By using a sophisticated in vivo magnetic resonance imaging approach we report the efficacy of CuII(atsm) in reducing acute cerebrovascular inflammation caused by peripheral administration of bacterial lipopolysaccharide. CuII(atsm) also induced anti-inflammatory outcomes in primary microglia (significant reductions in nitric oxide (NO), MCP-1 and TNF) and astrocytes (significantly reduced NO, MCP-1 and IL-6) in vitro. These anti-inflammatory actions were associated with increased cellular copper levels and increased the neuroprotective protein metallothionein-1 in microglia and astrocytes. Conclusions: The beneficial effects of CuII(atsm) on the neuroimmune system suggest copper complexes are potential therapeutics for the treatment of neuroinflammatory conditions.